Aerosol Gel production via controlled detonation of liquid precursors - Gilbertson, Sarah Elizabeth (Kansas State University, 2008)
This work emphasizes advancements in Aerosol Gelation. We have attempted to expand the available materials used to synthesize Aerosol Gels by moving away from gas phase precursors toward liquid phase precursors and eventually reactants in the solid phase. The primary challenge was to efficiently administer the liquid fuels into the detonation chamber. After several attempts, it was concluded that the most efficient delivery technique was to heat the liquid fuel past the vapor point and evaporate it into the oxidizing gas for combustion. This method consistently yields soot with a density of 3.2 mg/cc approximately 10 minutes after the combustion. It was concluded that four criterion must be met to create an Aerosol Gel from a liquid: 1. The liquid must be as finely divided as possible 2. The energy of the spark must be large enough to cause a sustainable combustion 3. The fuel must have a Lower Explosive Limit above the necessary concentration to meet a volume fraction of 10[superscript]4 4. The fuel must have a relatively low boiling point
Keywords: Aerosol; Gelation; Combustion; Low Density; Physics, Condensed Matter (0611)